Obesity in Children and Adolescents during COVID-19 Pandemic - Androniki Stavridou; Evangelia Kapsali; Eleni Panagouli; Athanasios Thirios; Konstantinos Polychronis; Flora Bacopoulou; Theodora Psaltopoulou; Maria Tsolia; Theodoros N. Sergentanis; Artemis Tsitsika (Children, 2021)
Background: The COVID-19 pandemic has led to special circumstances and changes to everyday life due to the worldwide measures that were imposed such as lockdowns. This review aims to evaluate obesity in children, adolescents and young adults during the COVID-19 pandemic. Methods: A literature search was conducted to evaluate pertinent studies up to 10 November 2020. Results: A total of 15 articles were eligible; 9 identified 17,028,111 children, adolescents and young adults from 5–25 years old, 5 pertained to studies with an age admixture (n = 20,521) and one study included parents with children 5–18 years old (n = 584). During the COVID-19 era, children, adolescents and young adults gained weight. Changes in dietary behaviors, increased food intake and unhealthy food choices including potatoes, meat and sugary drinks were noted during the ongoing COVID-19 pandemic. Food insecurity associated with financial reasons represents another concern. Moreover, as the restrictions imposed reduced movements out of the house, physical activity was limited, representing another risk factor for weight gain. Conclusions: COVID-19 restrictions disrupted the everyday routine of children, adolescents and young adults and elicited changes in their eating behaviors and physical activity. To protect them, health care providers should highlight the risk of obesity and provide prevention strategies, ensuring also parental participation. Worldwide policies, guidelines and precautionary measures should ideally be established.